Designing a Scale of Females’ Attitude towards Bodybuilding - Alyousef, Modar; Dreibati, Bachar; Alwazzah, Khaleel (Latakia University Journal -Medical Sciences Series, 2018)
The objective of this research is designing a scale of females’ attitude towards bodybuilding, as a questionnaire using a 5-point Likert scale. Methodology: The research is descriptive. The selected questionnaire dimensions were the components of the socio-psychological attitude (cognitive, emotional, and behavioral) where the cognitive dimension was subdivided into five subcategories (health, aesthetics, culture, psychology, and physical fitness). Then, 29 items were suggested, judged by experts, and applied on 50 female students at the Faculty of Physical Education in order to collect data and statistically analyze them using Cronbach’s Alpha to test reliability, and internal consistency and correlation with another scale that measures the same phenomenon to test validity (Stages of change scale). Results: The study resulted in eliminating 4 of the suggested items so that the scale became consisted of 25 items and 3 dimensions (cognitive, emotional, and behavioral) with the Cognitive dimension subdivided into 4 subcategories (health, aesthetics, psychology, and physical fitness). تصميم مقياس اتجاهات الإناث نحو بناء الأجسام يهدف البحث الحالي إلى تصميم مقياس اتجاهات الإناث نحو رياضة بناء الأجسام، على شكل استبيان بطريقة مقياس ليكرت الخماسي. المنهجية: يتبع البحث المنهج الوصفي، حيث حُددت ثلاثة أبعاد للاستبيان، هي مكونات الاتجاه النفس-اجتماعي (معرفي، عاطفي، سلوكي)، وتم تقسيم البعد المعرفي إلى خمسة محاور (صحي، جمالي، ثقافي، نفسي، اللياقة البدنية)، ثم تم اقتراح عبارات الاستبيان وهي 29 عبارة، وتحكيمها من الخبراء، وتطبيقها على عينة عشوائية من طالبات كلية التربية الرياضية مكونة من 50 طالبة، لجمع النتائج وإجراء الاختبارات الإحصائية اللازمة، وتم التأكد من الثبات عن طريق معامل ألفا كرونباخ، والصدق بطريقتي الاتساق الداخلي والارتباط بنتائج بمقياس آخر يقيس نفس الظاهرة (مقياس مراحل التغيير). النتائج: تلخصت نتائج الدراسة بحذف أربع عبارات من العبارات المُقترحة، ليصبح المقياس مُكوناً من 25 عبارة موزعة على ثلاثة أبعاد (معرفي، عاطفي، سلوكي)، والبعد المعرفي أصبح مُقسماً إلى أربعة محاور (صحي، جمالي، نفسي، اللياقة البدنية).